Mutations in the ganglioside-induced differentiation-associated protein-1 (GDAP1) gene in intermediate type autosomal recessive Charcot-Marie-Tooth neuropathy - Jan Senderek (2003)
Mutations in the gene for the ganglioside-induced differentiation-associated protein-1 (GDAP1) on 8q21 recently were reported to cause autosomal recessive Charcot-Marie-Tooth (CMT) sensorimotor neuropathy. Neurophysiology and nerve pathology were heterogeneous in these cases: a subset of GDAP1 mutations was associated with peripheral nerve demyelination, whereas others resulted in axonal degeneration. In this study, we identified two novel mutations disrupting the GDAP1 reading frame. Homozygosity for a single base pair insertion in exon 3 (c.349_350insT) was observed in affected children from a Turkish inbred pedigree. The other novel allele detected in a German patient was a homozygous mutation of the intron 4 donor splice site (c.579 + 1G>A). Patients with GDAP1 mutations displayed severe, early childhood-onset CMT neuropathy with prominent pes equinovarus deformity and impairment of hand muscles. Nerve conduction velocities were between 25 and 35 m/s and peripheral nerve pathology showed axonal as well as demyelinating changes. These findings fitted the definition of intermediate type CMT and further support the view that GDAP1 is vital for both, axonal integrity and Schwann cell properties.